(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A Computational Fluid Dynamics (CFD) based solver is used to numerically analyze the motion of a single spherical capsule in a horizontal hydraulic pipeline. A novel numerical model is employed with the aid of the dynamic mesh technique for calculating the pressure and the velocity of the moving capsule. The numerical model comprises a 2m long straight test section of 50mm diameter. The results from the numerical model were close to those from the experimental data from the test rig developed in the study. The capsule is assumed to be a point mass rigid body and the coaxial-annular-flow model around the capsule is used to derive the boundary conditions for water flow at the capsule discontinuity region. The results are compared with experimental work done.